Evaluation of image quality according to the use of copper filter in indirect conversion type DR equipment - Yu, Sinyoung; Choi, Joonkoo; Kim, Ghajung; GO, Joongseok; Chang, Kwanghyun; Kim, Seunggi (International Journal of Engineering and Technology, 2018)
Background/Objectives: The image quality is evaluated by applying copper to the thickness of filtering filter in indirect conversion type DR equipment. To evaluate the appropriate filter criteria, that does not deteriorate the image quality is obtained for SNR and CNR for each thickness.Methods/Statistical analysis: Indirect conversion type DR device was used. Acrylic phantom of 12 * 14 size was placed under the same conditions of 85kV, 200mA, 16ms.Experiments were carried out without using a filter, and each of the five copper filters of different thicknesses was irradiated 20 times each. Using the Image j program, an average value and a standard deviation were obtained after designating the region of interest and background area identically. Based on these values, SNR and CNR were obtained and statistical analysis was done by one-way ANOVA. Statistic was used PASW Statistics 18. Release 18.0.0.Findings: In the non-filter, the SNR value is 26.61 Â± 2.05, the CNR value is 0.61 Â± 0.06, the SNR value is 30.08 Â± 4, 63 and the CNR value is 0.76 Â± 0.16 for Cu-filter 0.1mm. In the Cu-filter 0.2 mm, the SNR value is 30.54 Â± 4.44, the CNR value is 0.78 Â± 0.16, and the SNR value at Cu-filter 0.3mm is 36.91 Â± 5.47 CNR value is 1.10 Â± 0.22. In the Cu-filter 1.0 mm, the SNR value is 24.88 Â± 2.57, the CNR value is 0.71 Â± 0.89, the SNR value is 13.82 Â± 1.27 and the CNR value is 0.31 Â± 0.02 at the Cu-filter 2.0 mm. The highest SNR was 0.3 mm, the highest CNR was 0.3 mm, and the Cu filter 0.3 mm was the highest in both SNR and CNR. There was a significant difference as the result of one-way ANOVA was P = 0.000 and significance level (p <0.05) range.Improvements/Applications: The use of a filter absorbs much of the low-energy region, The effective energy is increased and the radiation dose is reduced.Â Â